Analisis Faktor-Faktor Yang Mempengaruhi Penerimaan Pajak Bumi Dan Bangunan di Sumatera Barat - Muhammad Luthfi; Mike Triani (Jurnal Kajian Ekonomi dan Pembangunan, 2022)
This study aims to prove and analyze (1) the effect of gross domestic product on the realization of PBB in West Sumatra. (2) the amount of land to the realization of PBB in West Sumatra (3) building area to the realization of PBB in West Sumatra. (4) inflation on the realization of PBB in West Sumatra. (5) together with GRDP, total land area, building area and inflation towards the realization of PBB in West Sumatra. This type of research is quantitative research. In this study, the data used is panel data from 2015 – 2019 in 19 districts and cities in West Sumatra. The method used is a panel regression model with the selected panel regression estimation model, namely the Random Effect Model (REM.) The results obtained show that: (1) GRDP is not significant to the realization of PBB in West Sumatra (2 land area has a significant effect on the realization of PBB in Sumatra). West Sumatra (3) building area has a significant effect on PBB realization in West Sumatra (4) inflation is not significant on PBB realization in West Sumatra Together with GRDP, land area, building area and inflation have a significant effect on PBB in West Sumatra. the results of the study that the increasing number of people who own land and inflation is still under control, it actually encourages the realization of the payment of Land and Building Taxes in West Sumatra, therefore by observing the factors that encourage changes in the realization of PBB payments can provide a solution in the form of policies for local government to improve the actual value of land and building tax payments in 19 districts and cities in West Sumatra.